(Tragi)comedy of errors: state double and student plenums - Đukić, Vesna (Napredak, 2025)
The paper is based on the assumption that workers’ self-management as a road of leaving the “monopoly for power possession” of the state and party bodies developed a hybrid “state double” model as a Yugoslav predecessor of the anarcho-liberal idea of de-etatization, i.e., that self-management direct decision-making and financing social activities of common interest is the beginning of direct democracy of the plenums during the students’ university blockade. The research is aimed at perceiving the roadmap of the Yugoslav liberal “state double” model which has developed into a West-centric post-Yugoslav model of direct democracy of plenums as an alternative form of civic activism at the faculties and universities in Serbia. The research methodology is founded on the comparative historical analysis of the “state double” model in the sphere of social activities, starting from workers’ self-management. The empirical research refers to the alternative system of extra-institutional decision-making of the student plenums at the universities in Serbia supported by university professors and interested social groups which has articulated the crisis of democratization and institutionalization through introducing participatory and direct democracy of plenums.
Keywords: anarcho-liberalism; civil society; state double; social activities; comedy of errors; plenum; self-management; transition